Características sociodemográficas y su relación con la calidad de servicio financiero según el modelo SERVPERF en una entidad financiera - Marín García, Norma Liz (2023)
The main objective of the research was to identify the sociodemographic characteristics of financial clients related to their perception regarding the quality of service according to the SERVPERF model of the financial client of Compartamos Financiera, an agency located in the northeastern part of Peru, this study was developed under a methodology for basic, quantitative, descriptive research and non-experimental design; The technique for data collection was the survey in which the SERVPERF financial service quality measurement instrument was used in its validation into Spanish, this instrument is reliable according to Cronbach's Alpha whose coefficient was 0.926, which indicates high reliability; After considering the inclusion and exclusion criteria, a non-probabilistic sampling was considered with the participation of 330 clients, it is concluded that these clients' level of perception of the quality of financial service is at a medium level with 57.6%, highlighting the need to implement techniques that improve these results in order to improve customer perception